Shear bond strength and scanning electron microscopy characteristics of universal adhesive in primary tooth dentin: An in vitro study - Mahtab Memarpour; Fereshteh Shafiei; Faranak Razmjouei; Mina Soltani (Wolters Kluwer Medknow Publications, 2018)
Background: The aim of the study was to evaluate the adhesion of Scotchbond Universal Adhesive to primary tooth dentin by measuring shear bond strength (SBS) and observing morphological changes with scanning electron microscopy (SEM). Materials and Methods: In this in vitro study, a total of 60 primary canine teeth were randomly divided into 5 groups (n = 12). The study groups were (1) Phosphoric acid etching + Adper Single Bond 2 (control), (2) phosphoric acid etching + Scotchbond Universal (etch-and-rinse), (3) Scotchbond Universal (self-etch), (4) phosphoric acid etching + Scotchbond Universal + resin, and (5) Scotchbond Universal + resin. Composite cylinders were built on the tooth surface, and 10 samples in each group were selected for SBS testing and identification of the failure modes. Two samples from each group were observed by SEM. One-way ANOVA and Tukey honestly significant difference post hoc test were used for data analysis P value < 0.05 was considered statistically significant. Results: The results showed that SBS in Group 1 was significantly lower than in Groups 2, 3, and 4 (all P < 0.001). There was no significant difference between Groups 2 and 3 (P = 0.98), or between Groups 3 and 4 (P = 0.97). There was no significant difference between Groups 2 and 4 (P = 0.999) or between Groups 1 and 5 (P = 0.156). Mixed and cohesive failures were more frequent in Groups 2, 3 and 4. SEM observations showed that applying phosphoric acid to the dentin before Scotchbond Universal adhesive resulted in more open dentinal tubules and more resin tag impregnation. Conclusion: There was no significant difference in SBS between Scotchbond Universal Adhesive in etch-and-rinse and self-etching modes. The SBS of Scotchbond Universal Adhesive in etch-and-rinse mode was greater than Adper Single Bond 2.